Effects of Acupuncture and Moxibustion on Breast Cancer-Related Lymphedema: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (September 2021) - Gao, Yu; Ma, Tingting; Han, Mei; Yu, Mingwei; Wang, Xiuhui; Lv, Yiren; Wang, Xiaomin
Objective: The aim of this systematic review and meta-analysis of randomized controlled trials (RCTs) was to evaluate the effects of acupuncture and moxibustion (AM) in women with breast cancer-related lymphedema (BCRL). Methods: We retrieved RCTs published before January 24, 2021, from the MEDLINE, EMBASE, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Chongqing VIP (VIP), and Wanfang databases. RCTs that compared acupuncture and/or moxibustion intervention with other treatments were included. A random effects or fixed effects model was used based on the heterogeneity findings. Study quality was evaluated using the Cochrane risk of bias tool. Results: We included 14 RCTs in the analyses, of which 4 RCTs adopted acupuncture, 4 RCTs used moxibustion, and the rest used both. AM significantly reduced arm circumference at the elbow crease compared to routine care (Mean deviation (MD) = −7.26, 95% confidence interval (CI) = −8.30 to −6.21, P  < .00001). There was a significant difference between AM and diosmin tablets in the effective index for upper limb lymphedema (MD = 24.68, 95% CI = 24.82-30.53, P  < .00001), the range of motion of the shoulder during protraction (MD = 6.77, 95% CI = 2.81-10.73, P  = .0008), and adduction (MD = 4.17, 95% CI = 1.02-7.32, P  = .01). There was a significant difference between moxibustion and pneumatic circulation (MD = −0.51, 95% CI = −0.85 to −0.17, P  = .003) in the visual analog score (VAS) for swelling. Finally, compared to the blank control, acupuncture reduced the VAS for pain (MD = −1.33, 95% CI = −1.52 to −1.15, P  < .00001; heterogeneity ( I 2 ) = 0%, P  = .57). Conclusion: Our results suggest that AM is effective in the treatment of BCRL. AM may reduce arm circumference at the elbow crease (compared to routine care), increase effective index for upper limb lymphedema (compared to oral diosmin tablets), improve the range of motion of the shoulder during protraction and adduction (compared to oral diosmin tablets), and decrease the VAS for both swelling (compared to pneumatic circulation) and pain (compared to blank control).